Patients' information needs and attitudes about post-treatment surveillance for colorectal cancer in the United States: a multi-perspective, mixed methods study. Issue 8 (14th August 2019) - Lowenstein, Lisa M; Volk, Robert J; Cuddy, Amanda; Hempstead, Andrea P; You, Y Nancy; Van Loon, Katherine; Millas, Stefanos; Meyerhardt, Jeffrey A; Gavin, Patrick; Chang, George J
Abstract : Objective: We sought to determine patients' informational needs for post-treatment surveillance and elicit clinicians' and patient advocates' (ie, stakeholders) opinions regarding what patients should know about post-treatment surveillance in the USA. Design: A mixed-methods study, using semi-structured interviews followed by a survey study. Setting: Participants for the interviews were from two large academic medical centres and a safety-net hospital. The stakeholders were recruited from attendees at the Alliance for Clinical Trials in Oncology Network Spring 2016 meeting. Participants: Participants for the in-depth interviews were purposively sampled. Eligible patients were 6 months to 5 years post curative resection for colorectal cancer and were fluent in English. Participants for the anonymous survey were stakeholders. Main outcome(s) and measure(s): The main outcome was patients' with colorectal cancer informational needs for post-treatment surveillance, using an interview guide. The second outcome was the importance of the identified informational needs using an anonymous survey. Results: Of the 67 patients approached, 31 were interviewed (response rate=46%), the majority were between 1 and 3 years post-treatment (81%) and diagnosed at stage III (74%). Despite a desire to monitor for cancer recurrence, patients had little understanding of the concept of post-treatment surveillance, equating surveillance with screening and a belief that if a recurrence was found early there would be a higher likelihood of cure. The survey suggested that clinicians (n=38) and patient advocates (n=11) had some differing opinions regarding what patients should know about surveillance to be active in decisions. For example, compared with clinicians, patient advocates felt that patients should know recurrence treatment options (100% vs 58%) and likelihood for cure following recurrence treatment (100% vs 38%). Conclusions: The results of this exploratory mixed-methods study suggest that novel educational interventions targeting both patients and clinicians are needed to address the informational needs for post-treatment surveillance of colorectal cancer.